To pool or not to pool? Guidelines for pooling samples for use in surveillance testing of infectious diseases in aquatic animals. Issue 11 (21st October 2019) - Laurin, Emilie; Thakur, Krishna; Mohr, Peter G.; Hick, Paul; Crane, Mark St. J.; Gardner, Ian A.; Moody, Nicholas J. G.; Colling, Axel; Ernst, Ingo
Abstract: Samples from multiple animals may be pooled and tested to reduce costs of surveillance for infectious agents in aquatic animal populations. The primary advantage of pooling is increased population‐level coverage when prevalence is low (<10%) and the number of tests is fixed, because of increased likelihood of including target analyte from at least one infected animal in a tested pool. Important questions and a priori design considerations need to be addressed. Unfortunately, pooling recommendations in disease‐specific chapters of the 2018 OIE Aquatic Manual are incomplete and, except for amphibian chytrid fungus, are not supported by peer‐reviewed research. A systematic review identified only 12 peer‐reviewed aquatic diagnostic accuracy and surveillance studies using pooled samples. No clear patterns for pooling methods and characteristics were evident across reviewed studies, although most authors agreed there is a negative effect on detection. Therefore, our purpose was to review pooling procedures used in published aquatic infectious disease research, present evidence‐based guidelines, and provide simulated data examples for white spot syndrome virus in shrimp. A decision tree of pooling guidelines was developed for use by peer‐reviewed journals and research institutions for the design, statistical analysis and reporting of comparative accuracy studies of individual and pooled tests for surveillance purposes.